The Polemic of Adding the Term of Office for the Village Head in View from the Perception of Constitutional Law - Anang Dony Irawan; Ida Ayu Rosida; Ega Permatadani (Pancasila and Law Review, 2023)
Village administration is the spearhead of national economic development and resilience. In its history, the Village has received recognition by passing Law Number 6 of 2014 concerning Villages. Before the existence of the Village Law, the basis for recognition by the Village Government was only found in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This article tries to find out the forms of community participation in changing laws and regulations regarding Villages. In addition, it also examines the polemic over demands for an additional term of office for the Village Head, which has become the public spotlight from the perspective of Indonesian constitutional law. The type of research used in the preparation of this article is normative juridical with a statute approach and library research, by searching data and sources, which after that did a review and analysis until finally it was put in the form of writing of this article. Considering that Indonesia is a democratic country and not a communist country, where the communist government system seems authoritarian, and the term of office is long, the Village Law contains regulations regarding village authority and the term of office of the Village Head.